An air stable high temperature adhesive from modified SiBCN precursor synthesized via polymer-derived-ceramic route. Issue 7 (May 2018) - Luan, Xin'gang; Chang, Sen; Riedel, Ralf; Cheng, Laifei
Abstract: The high temperature adhesives are required in most critical applications such as nuclear and aerospace technology. To obtain an adhesive with high temperature bond strength and low synthesis temperature, polysilazane (PSNB) was modified by PBSZ, PSO, nano-Al2 O3 additives. Effect of the SiO2 to B2 O3 ratio and curing pressure on microstructure and high temperature bond strength has been investigated. After curing and heat-treating at comparatively lower temperatures, the bond strength of the modified adhesive reached up to 12.08 MPa, at room temperature, and, more significantly, retained the strength of 6.65 MPa at 1000 °C. The bond strength of modified adhesive is two-times higher than pure PSNB adhesive at elevated temperature. We demonstrate that optimum level of fluidity and applied pressure should be established in order to attain maximum bond strength. This paper open up avenues for further research in modifying existing adhesives for high temperature applications.